IMPROVING FIRE RESCUE IN COTTON AND TEXTILE ENTERPRISES - Assoc. Prof. Tukhtabayev S. T.; Assoc. Prof. Gapparova M. A. (Web of Journals Publishing, 2025)
The article examines the risks arising at cotton ginning and textile plants, fuel and lubricant warehouses, as well as in oil and petroleum product storage facilities. This solves the problem of increasing the heat resistance and fire resistance of structures, and also reduces the force of a strong shock wave, hydrodynamic flow wave, flame and high pressure generated during an explosion.
Keywords: Dust, fire, explosion, shock wave, building material, cement, construction, new generation additive, heat, flame.